Experience of establishing of the European insurance market - Sembekov, А.К.; Budeshov, Ye.G.; Tyngisheva, А.М. (BUKETOV BUSINESS REVIEW, 2017)
The article devoted to the study of European insurance market establishment and development experience. The authors found out regulatory and self-regulatory aspects of the European Union countries, considered the main forms of regulations, identified differences between insurance markets of the European Union countries. The study was carried out in the field of interstate controlling system for European insurance market. Based on the experience of the European Union insurance controlling system, authors identified the needs of consistent insurance controlling system establishment, within the framework of the Eurasian Economic Union, which can guarantee financial stability and protection against the risks of insurance services consumption. On result of the conducted research for creation of effective system of controlling of the Euroasian insurance market by authors the following recommendations are offered: creation of committee on risk management, formation of the general body of interstate insurance controlling, creation of interstate self-regulating insurance associations. This article was published within the framework of the scientific project, named «Competitiveness of the National Insurance Market against the backdrop of the EAEU integration» (3988/GF4) and intended for scientific research. Scope of results: results of a research can be used by bodies of interstate regulation of the EAEU for creation of effective system of insurance controlling.